ナンキョク サン ビサイ ソウルイ ノ バイヨウ 2 ナンキョク スカルブスネス ノ エンコ カラ ブンリ シタ ACHNANTHES BREVIPES AGARDH VAR INTERMEDIA KUTZ CLEVE - 綿貫, 知彦; ワタヌキ, トモヒコ; 大野, 正夫; オオノ, マサオ; WATANUKI, Tomohiko; OHNO, Masao (国立極地研究所, 1975)
P(論文) The Lake Hunazoko and Lake Suribati are salt lakes in the Skarvsnes of the coastal region of Liitzow-Holm Bay, Antarctica. The cloride contents of Lake Hunazoko varied from 73 g Cl/l to 143 g Cl/l in a season, and those of Lake Suribati also varied from 25 g Cl/l to 73 g Cl/l. Achnanthes brevipes AGARDH var. intermedia (Kuxz.) CLEVE was isolated from the samples of the bottom sand which were collected on the coast of these lakes, from 28 to 29 January 1975. This species, being distributed in the fresh water over the world widely, was now reported from the salt lakes in Antarctica. departmental bulletin paper